Aplikasi Katalis α-MnO2-400 Yang Dikalsinasi Pada Temperatur 400oc Untuk Degradasi Kandungan Organik Limbah Cair Industri Pulp Dan Kertas - Peji Nopeles; Edy Saputra; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The pulp and paper industry is a water-intensive industry, and number third in the world and also a significant contributor to pollutant discharge to the environment. It is know that the low COD/BOD ratio obtained from pulp industry wastewater is an average of 0.3 while the ideal of biodegradability value is in the range above 0.5. Thus, there are alternative treatments that can degrade hazardous compounds in wastewater that are slow to degrade through the oxidation process, known as the Advanced Oxidation Process (AOP). AOP is based on active radicals which are produced as oxidizing agents to mineralize the complex chemical substance in the wastewater. One of the active radicals, known sulfate radicals (SO4*), has a high oxidation potential of 2.5 – 3.1 V. Several studies showed that radical sulfates can be produced by catalytic oxodation process, such as combination of Peroxymonosulfate with homogeneous metal ion catalyst (Fe2+, Mn2+, Ni 2+, Co2+, Cd2+, Cu2+, Ag+1, Cr3+, Zn2+). In this study, AOP method peroxymonosulfate which was activated with the catalyst α-MnO2-400 were used to treat organic content in wastewater of pulp and paper industry. The α-MnO2-400 catalyst was produced from 1:3 molar potassium permanganate (KMnO4) and maleic acid that calcined at 400oC. This catalyst was characterized by XRD, BET and FESEM. From XRD analysis obtained the peak aligned with JCPDS Standard. From the BET analysis obtained surface area is 49.17 m2/g, pore size 6.4 nm and pore total 0,16 cm3/g. From FESEM analysis obtained crystalit structured with average length 21 nm. The best degradation of COD and TOC concentration obtained at temperature 45oC, at retention time 240 minutes, with peroxymonosulfate concentration 2,0 g/L and catalyst concentration 0,4 g/L (73% and 77%). Key word: AOP, Catalyst, COD, Peroxymonosulfate, Waste water